Hypertrophic obstructive cardiomyopathy. Assessment by echocardiographic and Doppler ultrasound techniques. Issue 9 (September 1975) - Boughner, D R; Schuld, R L; Persaud, J A
Abstract : Hypertrophic obstructive cardiomyopathy is a disease of the myocardium that can be assessed echocardiographic and transcutaneous Doppler ultrasound techniques. Four patients are presented with various patterns of the disease, and the frequently familial incidence is illustrated. The importance of ultrasonic evidence for asymmetric septal hypertrophy in all stages is emphasized and evidence of reduced septal contractility demonstrated. Abnormalities of mitral valve motion, slow diastolic closure rate and systolic anterior movement of the anterior leaflet, are shown in the obstructive form of the disease. Also partial mid-systolic aortic valve closure and aortic cusp flutter are shown with outflow obstruction. The outflow tract gradient can be calculated from mitral valve to septum systolic distances. Transcutaneous Doppler ultrasound shows a normal aortic velocity pattern in nonobstructive disease while consistent abnormalities are present with severe resting obstruction. Isoprenaline can be used to alter the normal velocity pattern associated with a minimal resting gradient to an abnormal pattern indicating the development of significant obstruction.